Coronary Anomalies: Left Main Coronary Artery Aneurysm - Rajsekhar Varda; Santosh Kumar Chitimilla; Aslam Lalani (Case Reports in Cardiology)
Coronary artery aneurysm is one of the rarest anomalies that we see in our medical practice and they are mostly associated with obstructive lesions due to atherosclerotic changes. Management of these aneurysm patients (conservative or surgical repair) usually depends on obstructive lesions and associated symptoms. We are presenting a case of left main aneurysm measuring around 14×28 mm with other obstructive leisons. It was treated with surgical repair in view of obstructive lesions and symptoms.